THE USED OF MORPH IN WORD PRONUNCIATION THROUGH ‘TONGUE TWISTER’ GAME - Fahmi Tri Prastyo; Intan Satriani (PROJECT (Professional Journal of English Education), 2023)
One of the basic skills in English is Speaking. In speaking, students have to know the pronunciation of the word. For some students, pronouncing words can be problematic. Morph can help the students to do the correct pronunciation because, with morph, the students can learn pronunciation through phonetic symbols. With tongue twister, learning morph can be interesting. This research method was action research where the researcher conducted a test on the participants. The researcher did this research In English Department Study Program at Private University in Cimahi. The participants of this research were students in the 5th semester. The researcher gave the participants three levels of Tongue Twister to know either the vowel or consonant have more errors when it is pronounced. After did the research, the researcher got the data. The researcher found that /ð/ symbol and /f/ symbol often error while the participants read the tongue twister. Thus, with Tongue Twister, teaching word pronouncing can be more attractive and can replace the general teaching method. Keywords:  Pronunciation; Morph; Tongue Twister Game